Elution features of sorptive generators technetium-99m; European Journal of Nuclear Medicine and Molecular Imaging; Vol. 42, suppl. 1 : European Association of Nuclear Medicine, EANM'15 - Rogov A. S. Alexander Sergeyevich; Skuridin V. S. Viktor Sergeyevich; Stasyuk (Stasiuk) E. S. Elena Sergeyevna; Nesterov E. A. Evgeny Alexandrovich; Varlamova N. V. Natalya Valeryevna; Sadkin V. L. Vladimir Leonidovich; Larionova L. A. Lyudmila Aleksandrovna; Ilyina E. A. Ekaterina Alekseevna (2015, 2015)
Title screen